PERCEPATAN PENERBITAN IZIN UMKM DESA MUKTI KARYA MELALUI PROGRAM APLIKASI TEORI EKONOMI PEDESAAN STAIDA SUM-SEL - Tasurun Amma; Wasil; Yarkasih; Imam Tobroni; Putri Lestari; Nana Mardiana (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
STAIDA Sumatera Selatan’s rural economic theory application program carries out socialization and assistance in implementing accelerated licensing of UMKM in Mukti Karya with the aim of finding out how many UMKM owners there are in Mukti Karya, what fields of UMKM are carried out by the Mukti Karya village community, and assisting with applications UMKM licensing run by the community. The stages in implementing socialization activities and assistance in accelerating UMKM licensing are carried out in 3 stages, namely; Data collection and socialization, at this stage, coordination activities are carried out with local village officials, visiting UMKM locations, socializing and deepening licensing and development issues with UMKM owners, and summarizing the results and determining work steps to accelerate UMKM licensing. Implementation of business licensing applications, at this stage, activities are carried out to collect required documents for applying for business permits, seeking solutions to obstacles to required documents, and applying for permits together with UMKM owners. Submission of Business Licenses and Evaluation, at this stage the results of the activities are the submission of business licenses to UMKM owners, suggestions for UMKM development, and performance evaluation. So that the Business Identification Number is generated by three business owners and banners are installed, namely the Donut business, Tempe business, and Tofu business.